Psoriasis risk allele function in activated Th1/17 cells with “memory” to antigen exposure - Bayazit Yunusbayev; Sergei Ryakhovsky; Radick Altinbaev; Anastasia Kislova; Kseniya Danilko; Liudmila Kraeva; Milyausha Yunusbaeva (PLoS ONE, 2026)
Most causal variants for complex diseases are expected to affect gene regulation in a cell- and context-specific manner. Hence, identification of such dynamically functioning variants requires functional readouts in disease-relevant tissues and context. In this study, we prioritized causal variants for psoriasis by adding functional annotations from disease-relevant cells. We demonstrate that disease-relevant immune cells, unlike most other tissues, possess functional annotations that match candidate causal SNPs. Specifically, we identified an eQTL, rs4672505, that reduces B3GNT2 gene expression only in Th1/Th17 cells with a memory phenotype, i.e., antigen-experienced T helper cells. This eQTL, a likely causal variant, also matched an enhancer chromatin mark exclusive to memory T helper cells and absent in other tissues. A disease-risk allele A at the eQTL correlates with reduced expression of the B3GNT2 glycosyltransferase. B3GNT2 deficiency in murine models reduces the glycosylation of the CD28 co-receptor involved in the CD28/B7 co-stimulation pathway and results in increased T cell activation upon antigen stimulation. We hypothesize that the risk allele A in patients increases the activation of memory Th1/Th17 cells upon re-exposure to antigens, which constitutes “signal 1”. Increased reactivity to antigens depends on “signal 2” via CD28/B7 co-stimulation from antigen-presenting cells that need to encounter microbial products. Hence, this genetic risk mechanism lies at the nexus of the response to specific antigens and microbial exposure, for instance, infection or vaccination, both of which are known to exacerbate psoriasis.